2019
DOI: 10.1080/2159676x.2019.1595105
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of sitting in the context of chronic disease: a critical reflection on sedentary behaviour, health, choice and enjoyment

Abstract: Reducing sedentary behaviour or sitting is a new public health focus. Emerging research has, however, found that sedentary activities may be associated with health and mental health benefits for older adults. This article reports findings of the qualitative arm of a feasibility trial to reduce sedentary behaviour among patients with Chronic Obstructive Pulmonary Disease (COPD). From interviews (n=21) conducted prior to the intervention we identified three themes: (i) participants sat to enable them to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…A 2020 study exploring SB and chronic illness highlighted the need to be aware of the important balance between encouraging a reduction in SB to obtain health-benefit alongside recognition of the importance of chronically ill patients engaging in sedentary activities they gain pleasure from, particularly given the physical limitations they may experience [32]. This aligns with our current findings, and those reported in our patient and caregiver paper [30].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A 2020 study exploring SB and chronic illness highlighted the need to be aware of the important balance between encouraging a reduction in SB to obtain health-benefit alongside recognition of the importance of chronically ill patients engaging in sedentary activities they gain pleasure from, particularly given the physical limitations they may experience [32]. This aligns with our current findings, and those reported in our patient and caregiver paper [30].…”
Section: Discussionsupporting
confidence: 83%
“…A 2019 systematic review exploring adults' experiences of SB and non-workplace interventions also found that "cultural habits" can form based on feeling entitled to spend more time resting in later life, or after a hard day's work. These findings are similar to the study exploring chronic illness and SB [32], which found limitations and facilitators to reducing SB that are directly linked to chronic illness, as well as appreciation of encouraging engagement with activities that provide enjoyment, and recommended any interventions developed to reduce SB should consider these factors [33].…”
Section: Discussionsupporting
confidence: 82%
“…In terms of health promotion practices and engagement, the differing forms of habitus outlined here illustrate the pitfalls of health messaging which focusses on individual health behaviour, for this often does not take into account local understandings of health or may be at odds with them. Favoured current health promotion programmes tend to be individualistic, focusing on changing individuals’ behaviour, sometimes incorporating new innovations and initiatives, such as self‐tracking (Copelton, 2010; Harries & Rettie, 2016; Weedon et al 2020) and cycling (Nettleton & Green, 2014). As our material demonstrates, however, individualistic interventions are apt to be perceived as alien and unlikely to fit the habitus of many residents, as illuminated by the humour expressed by older adults about doing press‐ups and the sense that local people would not want carrots or lentils.…”
Section: Discussionmentioning
confidence: 99%
“…The practices were also a source of distinction between participants and their home‐bound peers supported by carers. Thus, rather than being redolent of unhealthy conduct, such as drinking and being sedentary, the activities described were part of a highly valued and often precarious ability to enjoy life in old age by being mobile, independent and able to socialise, and thus maintaining this habitus was an important signifier of wellbeing (see also Weedon et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers working with individuals with chronic obstructive pulmonary disease have cautioned the messaging of SitLess as challenging for those who have good reasons for needing to sit (ie, to rest and enable other activities). 31 A priori, we were cognizant that an intervention using messaging to break up sitting time frequently was opposite to the energy conservation message often delivered to individuals with MS. 32 We report reductions in fatigue with this intervention, thus our study suggests that concerns of greater amounts of fatigue with an intervention that focused on sitting less and moving more were unwarranted. Nevertheless, clinicians must recognize and communicate their understanding of the reasons to sit, and help patients to set achievable goals related to sitting less.…”
Section: Discussionmentioning
confidence: 99%